Report on Adjunct Prof Abdul Halim Ali visit to the Faculty of Social Sciences 10-17 March 2013 - Sharifah S., Wan Ahmad (Faculty of Social Sciences, 2013)
For the visit, there were two main objectives identified. The first objective was to continue on the agenda for publication of edited volume of essays consisted of young academics in the faculty. The second objective was to provide academic training for students and staff through lecture and reading circles.